Enhanced Expression of Human Epididymis Protein 4 (HE4) Reflecting Pro-Inflammatory Status Is Regulated by CFTR in Cystic Fibrosis Bronchial Epithelial Cells - Bene, Zsolt; Fejes, Zsolt; Szanto, Tibor Gabor; Fenyvesi, Ferenc; Váradi, Judit; Clarke, Luka A.; Panyi, Gyorgy; Macek, Milan; Amaral, Margarida D.; Balogh, István; Nagy, Béla (Frontiers in Pharmacology, 2021)
Decreased human epididymis protein 4 (HE4) plasma levels were reported in cystic fibrosis (CF) patients under CFTR potentiator ivacaftor therapy, which inversely correlated with lung function improvement. In this study, we investigated whether HE4 expression was affected via modulation of CFTR function in CF bronchial epithelial (CFBE) cells in vitro. HE4 protein levels were measured in the supernatants of CFBE 41o- cells expressing F508del-CFTR or wild-type CFTR (wt-CFTR) after administration of lumacaftor/ivacaftor or tezacaftor/ivacaftor, while HE4 expression in CFBE 41o- cells were also analyzed following application of adenylate cyclase activators Forskolin/IBMX or CFTRinh172. The effect of all of these compounds on CFTR function was monitored by the whole-cell patch-clamp technique. Induced HE4 expression was studied with interleukin-6 (IL-6) in F508del-CFTR CFBE 41o- cells under TNF-a stimulation for 1 hour up to 1 week in duration. In parallel, plasma HE4 was determined in CF subjects homozygous for p.Phe508del-CFTR mutation receiving lumacaftor/ivacaftor (Orkambi) therapy. NF-κB-mediated signaling was observed via the nuclear translocation of p65 subunit by fluorescence microscopy together with the analysis of IL-6 expression by an immunoassay. In addition, HE4 expression was examined after NF-κB pathway inhibitor BAY 11-7082 treatment with or without CFTR modulators. CFTR modulators partially restored the activity of F508del-CFTR and reduced HE4 concentration was found in F508del-CFTR CFBE 41o- cells that was close to what we observed in CFBE 41o- cells with wt-CFTR. These data were in agreement with decreased plasma HE4 concentrations in CF patients treated with Orkambi. Furthermore, CFTR inhibitor induced elevated HE4 levels, while CFTR activator Forskolin/IBMX downregulated HE4 in the cell cultures and these effects were more pronounced in the presence of CFTR modulators. Higher activation level of baseline and TNF-a stimulated NF-κB pathway was detected in F508del-CFTR vs. wt-CFTR CFBE 41o- cells that was substantially reduced by CFTR modulators based on lower p65 nuclear positivity and IL-6 levels. Finally, HE4 expression was upregulated by TNF-a with elevated IL-6, and both protein levels were suppressed by combined administration of NF-κB pathway inhibitor and CFTR modulators in CFBE 41o- cells. In conclusion, CFTR dysfunction contributes to abnormal HE4 expression via NF-κB in CF.